Error Analysis in Numerical Simulation of the Static Pressure Capability of Magnetic Fluid Seals - Li, Zhenghao; Li, Decai (Frontiers in Materials, 2022)
Magnetic fluid is a typical type of functional fluid which can be magnetized and controlled by an external magnetic field. In magnetic fluid seals, magnetic fluid is attracted in sealing gaps by magnetic field gradient to form non-contact sealing. Compared to traditional sealing methods, they possess unique advantages such as zero leakage, long lifetime, low friction torque and high reliability. Although the design and performance estimation of magnetic fluid seals rely mostly on numerical simulation, a number of simplifications or even mistakes during simulation process exist in previous studies. The error caused by simplifications and mistakes has not been studied, leading to a possible problem of simulation results in reliability and consistency with experimental data. Here we examine the influence of common simplifications and mistakes in numerical simulation of static pressure capability of magnetic fluid seals, including material properties, geometric modeling and theoretical formulas. A novel method of structure optimization based on derivative-free multiparameter algorithm is also presented. A test bench for magnetic fluid seals is established, and the difference between simulation and experimental results is discussed. This research provides a precise, efficient and standard procedure for numerical simulation of magnetic fluid seals.